CPB3. Abiotic Screening and Molecular Characterization of BADH, Fragrance Gene from Aromatic Rice Accessions (2018)
Fragrance or aroma is one of the most valuable quality in rice grain. The 2-acetyl-1 pyrroline (2AP), the known compound that contributes to the aroma in rice is synthesized through the loss of functional enzyme of Betaine Aldehyde Dehydrogenase 2 (BADH2). Interestingly, another gene present in rice, known as BADH1 a homologous gene of BADH2 is involved with the synthesis of glycine betaine (GB) enables the accumulation of y-aminobutyraldehyde (GABald) to form 2AP. The synthesis of y-aminobutyric acid (GABA) from GABald is related with salt and drought stress response of the plant. In this study, initial information on salinity stress tolerance were gathered from twenty-four (24) selected aromatic rice accessions from Central Luzon State University. Leyte special accession was recorded as moderately tolerant among the selected aromatic rice accession with significant compared to tolerant check variety Pokkali after 8-days from pre-conditioning and 5-days from salinization using modified standard evaluation system for scoring of visual salt injury. The selected aromatic rice accessions were also currently being screened under drought stress condition to evaluate their respective response to the stress. The characterization of BADH1 gene in selected aromatic accession is also underway to generate more information about the role of BADH1 to rice aroma and stress response using genomic and transcriptomic information.